Факторы увеличения эффективности пленочного охлаждения за двухрядной системой отверстий в полусферических углублениях - Халатов, Артем Артемович; Панченко, Надежда Анатольевна; Безлюдная, Мария Владимировна (НТУ "ХПИ", 2017)
Представлены результаты поверхностной визуализации и компьютерного моделирования пленочного охлаждения плоской поверхности при подаче воздуха через цилиндрические наклонные отверстия в полусферических углублениях и через традиционные цилиндрические наклонные отверстия. На основании анализа результатов сделаны выводы о структуре течения за отверстиями в сферических углублениях и о причинах повышения эффективности пленочного охлаждения за ней по сравнению с традиционной схемой.

The modern high-performance gas turbine engines operate at the temperatures exceeding the melting temperature of construction materials, which require the blade cooling. Usually the gas turbine blades apply high-developed cooling system including the external film cooling promoting the higher operational durability and longer blade service life. Then film cooling efficiency depends strongly from the method of coolant supply onto the blade surface. Currently the published results contain some data, regarding the type of coolant supply. Analysis of this data has shown that coolant supply into hemispherical dimple is one of the perspective schemes, providing the high rate of film cooling efficiency. The interesting scientific task is investigation of physical structure near the cooled surface and identification of reasons influencing greater film cooling efficiency compared with traditional cooling technique. For this reason using the ink spot technique the surface streamline visualization was performed for the traditional cooling scheme, as well as the coolant supply into hemispherical dimples. The numerical simulation was made using ANSYS CFX 14 code along with k-e turbulence model, the blowing factor was varied from 0.5 to 2.0. The analysis of results obtained has shown that scheme with a coolant supply into hemispherical dimples reduces the flow separation length and the intensity of pair ("kidney") vortex.
Augmentation factors of the film cooling configuration using two rows of inclined cylindrical holes placed inside hemispherical dimples
Keywords: вихрь почечный; визуализация; моделирование компьютерное; линии тока; film cooling; spherical dimples; kidney vortex; visualization; numerical simulation; surface streamlines